Understanding the expectations of nursing students following the first clinical internship: A qualitative study - Leyva-Mora, Juan M. (2022)
“This study aimed to describe how nursing students' expectations are achieved in their first clinical internship, as part of a longitudinal qualitative study conducted in a public nursing school in Barcelona, Spain. Data in the current phase were collected in 2019 from students (n = 15) after completing an internship for the first time, recruited with purposive sampling until data saturation was reached in semi-structured interviews, and thematic analysis was performed on the interview content. Positive factors that had a powerful influence on students included the accessibility at the internship location and the experience with the clinical instructor, when these provided assessment and integration of the student in the health team. Practical learning is mediated by chance in terms of the center, service, teacher, and clinical instructor assigned. It is crucial to establish consensual measures among all the actors involved to facilitate the efficacy of teaching and learning.“